Marker-assisted breeding of hybrid lines of Triticum dicoccon (Schrank) Schuebl. × Triticum aethiopicum Jakubz. with purple grain - P. I. Stepochkin; E. I. Gordeeva; Е. K. Khlestkina (Труды по прикладной ботанике, генетике и селекции, 2023)
Background. Cereals whose grain contains antioxidants salutary for human health are promising for functional nutrition. Anthocyanins inducing purple grain color are antioxidants, and it is crucial to make efforts towards increasing their content in grain.  The objective of this work was to assess the content of anthocyanins in emmer grain and the productivity of breeding lines with purple grain.   Materials and methods. The study included the F9 lines developed by two-step hybridization between purple-colored Ethiopian wheat (Triticum aethiopicum Jakubz. var. arraseita) and emmer (Triticum dicoccon (Schrank) Schuebl.), and those isolated in F2 using marker-based selection for homozygous dominant alleles of two genes. The parent forms of the hybrids were a naked-grain emmer cultivar ‘Gremme’, an awnless emmer accession (k-25516) from the VIR collection, and an accession from the collection of IPK Gatersleben (Ethiopian wheat line TRI 15744), the donor of the purple color. The content of anthocyanins in whole-grain flour was measured in 12 lines, a structural analysis of plants was carried out, and their quantitative characteristics were assessed.   Results. The highest anthocyanin content (82.5 µg per 1 g) was observed in line No. 10 of the 27-3 hybrid. The largest share of threshed naked grains (86.9 ± 7.3 %) was recorded for line No. 6 of the 31-19 hybrid. Line No. 11 of the 27-12 hybrid had the highest test weight (802 ± 13 g/L). Line No. 9 of the 27-1 hybrid showed the best index of grain productivity (389 ± 25 g/m2).   Conclusion. Marker-assisted selection made it possible to identify homozygous dominant alleles of the two complementary interacting genes, Pp3 and Pp-B1, which cause the purple color of the grain pericarp. Breeding lines with purple-colored grain demonstrated different levels of the total anthocyanin content, test weight, and grain yield. The lines with high indices of these traits are valuable for breeding practice.